2017
DOI: 10.1002/marc.201600684
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Water‐Soluble Fluorescence Probe with Wash‐Free Cellular Imaging Capacity Based on AIE Characteristics

Abstract: A potential real-time imaging water-soluble fluorescent polymer (P3) is facilely prepared via one-pot method. For P3, tetraphenylethene unit serves as the fluorescent unit, poly(acryloyl ethylene diamine) (a kind of polyelectrolyte) with specific degree of polymerization acts as water-soluble part. H-NMR, gel permeation chromatography (GPC), UV-vis spectroscopy, photoluminescence (PL), and confocal laser scanning microscopy are undertaken to characterize the structure and property of P3. The results of wash-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…However, for the PEG‐PEI‐TPE/SPIO probe, the core is PAA‐coated SPIO; hence, the aggregation of TPE in PEG‐PEI‐TPE/SPIO should occur around the SPIO core in water, which is responsible for the stacking and RIR process of TPE [Scheme (c)]. A number of factors such as the concentration, hydrophobicity, rigidity, and chain length of TPE incorporated polymers, and the temperature and viscosity of the TPE solution will affect the RIR process of TPE, namely, influence the fluorescence properties of TPE . As a result, there may be three possible reasons that can explain why the fluorescence intensity and lifetime of PEG‐PEI‐TPE/SPIO is longer than PEG‐PEI‐TPE, especially at lower concentrations: first, SPIO can be considered as a core crosslinking agent of PEG‐PEI‐TPE, which may improve the stability of aggregates of TPE; second, the crosslinking of PEG‐PEI‐TPE may help to bring TPE closer, which will further promote the RIR process; thirdly, the polymer chain of PAA becomes more hydrophobic after coupled by PEG‐PEI‐TPE.…”
Section: Resultsmentioning
confidence: 99%
“…However, for the PEG‐PEI‐TPE/SPIO probe, the core is PAA‐coated SPIO; hence, the aggregation of TPE in PEG‐PEI‐TPE/SPIO should occur around the SPIO core in water, which is responsible for the stacking and RIR process of TPE [Scheme (c)]. A number of factors such as the concentration, hydrophobicity, rigidity, and chain length of TPE incorporated polymers, and the temperature and viscosity of the TPE solution will affect the RIR process of TPE, namely, influence the fluorescence properties of TPE . As a result, there may be three possible reasons that can explain why the fluorescence intensity and lifetime of PEG‐PEI‐TPE/SPIO is longer than PEG‐PEI‐TPE, especially at lower concentrations: first, SPIO can be considered as a core crosslinking agent of PEG‐PEI‐TPE, which may improve the stability of aggregates of TPE; second, the crosslinking of PEG‐PEI‐TPE may help to bring TPE closer, which will further promote the RIR process; thirdly, the polymer chain of PAA becomes more hydrophobic after coupled by PEG‐PEI‐TPE.…”
Section: Resultsmentioning
confidence: 99%
“…Ther esults demonstrated that DBTAc ould easily enter biological samples including living cells and fish larva, and showed excellent signal to noise ratio without washing the unstained dye.D BTAi sm uch easier to access than the existing AIE wash-free imaging systems. [26,27] In summary,w eh ave developed an ovel water-soluble ionic AIEgen DBTAb yasimple one step reaction with adecent yield. Thefacile access of DBTAisvery attractive in terms of saving time,labor,and economy cost.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Without washing,t he fluorescence image was collected by staining with DBTAfor 30 min, which showed strong fluorescence in HeLa cells and negligible background fluorescence.I nsharp contrast, the fluorescence image obtained by incubation with Cy3 dye exhibited strong fluorescence in the whole imaging area. [26,27] In summary,w eh ave developed an ovel water-soluble ionic AIEgen DBTAb yasimple one step reaction with adecent yield. Thef luorescence image collected without washing showed bright blue-greenish fluorescence inside the fish larva and almost no background signal.…”
mentioning
confidence: 99%
“…The results demonstrated that DBTA could easily enter biological samples including living cells and fish larva, and showed excellent signal to noise ratio without washing the unstained dye. DBTA is much easier to access than the existing AIE wash‐free imaging systems …”
Section: Figurementioning
confidence: 99%